Unilateral chewing of foods. Analysis of energy balance and peak power of the mandibular elevator muscles - Stróżyk, Przemysław; Bałchanowski, Jacek (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction: The paper presents the results concerning the energy (work) and peak power generated by the elevator muscles of the mandible (the masseter, medial pterygoid, and temporalis muscles) during unilateral chewing of selected food products in vitro. Since the act of chewing is a very complex issue in the biomechanics of the masticatory system, the research and analysis of the obtained results were therefore limited to the first cycle.Methods: Determination of the peak energy and power of the muscles required: (1) preparation of food patterns, in the form of the function F = f(Δh) (force (F) vs displacement (Δh)), based on experimental studies and (2) conducting numerical simulations using a 3D kinematic-dynamic model of the human masticatory system. Results and Discussion: Based on the results, the peak energy and power of the muscles were determined based on food patterns. A comparative analysis was also performed to evaluate the energy and peak power generated by the aforementioned muscles during symmetrical incisal biting vs unilateral chewing of the same food products. The results indicate that (1) food height and texture significantly affect muscle energy and (2) the masticatory and medial pterygoid muscles generate more incredible energy and peak power on the working side than on the non working side, while the opposite was observed for the temporalis muscle and (3) comparative analysis showed that food position on the dental arch has a more significant effect on muscle peak power for foods with high texture heterogeneity than for foods with low texture heterogeneity.